Improved depression screening and treatment among low-income pregnant and postpartum women following Medicaid expansion in the U.S - Yoon, Jangho; Harvey, S. Marie; Luck, Jeff (Frontiers in Health Services, 2022)
Objective: This study examined the effect of Medicaid expansion in Oregon under the Affordable Care Act on depression screening and treatment among pregnant and postpartum women who gave Medicaid-financed births. Method: Oregon birth certificates were linked to Medicaid enrollment and claims records for 2011-2016. The sample included a policy group of 1,368 women (n = 2,831) who gave births covered by pregnancy-only Medicaid in the pre-expansion period (before 2014) and full-scope Medicaid in the post-expansion period, and the comparison group of 2,229 women (n = 4,580) who gave births covered by full-scope Medicaid in both pre- and post-expansion periods. Outcomes included indicators for depression screening, psychotherapy, pharmacotherapy, and combined psychotherapy-pharmacotherapy, separately for the first, second, and third trimesters, and two and six months postpartum. This study utilized a difference-in-differences approach that compared pre-post change in an outcome for the policy group to a counterfactual pre-post change from the comparison group. Results: Medicaid expansion led to a 3.37 percentage-point increase in the rate of depression screening six months postpartum, 4.28 percentage-point increase in the rate of psychotherapy six months postpartum, and 2.3 and 1 percentage-point increases in the rates of pharmacotherapy and combined treatment in the first trimester, respectively. The relationships were driven by disproportionate gains among non-Hispanic whites and urban residents. Conclusions: Expanding Medicaid eligibility may improve depression screening and treatment among low-income women early in pregnancy and/or beyond the usual two-month postpartum period. However, it does not necessarily reduce racial/ethnic and regional gaps in depression screening and treatment.